Pengaruh waktu pemolesan terhadap perubahan warna resin komposit nano partikel setelah perendaman larutan obat kumur - Iin Sundari; Sri Fitriyani; Cut Zahratul (Jurnal Material Kedokteran Gigi, 2012)
Finishing refers to all the procedures associated with shaping, contouring, and polishing. Polishing immediately after restoration composite resin placement is most clinicians performance. Polishing time can effect strength of composite resin restoration. Immediate polishing may increase on both the surface roughness and the water sorption compared to delayed polishing for 24 hours and may lead to color change of composite resin restoration. The objectives of this study was to evaluate the effect of polishing time on color stability of composite resin nano particle after immersion in mouthwash. This research is experimental laboratory design. Total specimen were 20 and divided in two group. The first group was polished immediately and the second group was polished after 24 hours (n=10). Polishing was done by using Enhance (aluminium oxide) with low speed handspiece 15,000 rpm for 15 second. The specimens were immersed in 20 ml herbal mouthwash for 360 minutes. Color measurement of specimen before and after immersion was obtained by stereomicroscope modified with camera digital and used Adobe Photoshop 7.0 program for evaluate L, a, and b value. The L, a, and b value were input in CIELab (Commission Internationale de l’Eclairage L, a, b) formula with ∆E parameter. Data were analyzed using Independent T-test at a significance level of 0,05. Analysis result of Independent T-test showed that there is significant difference of color change value of composite resin polished immediately is higher than delayed polish for 24 hours. Immediately and delayed for 24 hours can effect on color stability of composite resin nano particle. ∆E value in this research was about 0-2 (∆E<3,7), so color change after immersion in herbal mouthwash was not visual perceptible.